Marketing para el posicionamiento de la marca “Blues Resto Bar” provincia Bolívar, ciudad de Guaranda, Periodo 2025 – 2030 - Monar Benavides, Jordan Lenin (2025)
Currently, marketing is a fundamental tool for strengthening brand positioning in an increasingly competitive market. Blues Resto Bar, located in Guaranda, offers an attractive gastronomic proposal but faces weaknesses in its brand positioning due to its limited digital presence and communication strategies. The general objective of this research was to determine the marketing actions for the brand positioning of Blues Resto Bar in the city of Guaranda during the period 2025–2030. For this purpose, a mixed methodology with both quantitative and qualitative approaches was used, applying surveys to 128 people and conducting interviews with the restaurant's management team. The results revealed that a high percentage of the population does not know about the restaurant due to a lack of advertising and visibility on social media. Although the products offered are positively valued, the business relies on word-of-mouth and lacks segmented marketing campaigns. Additionally, respondents indicated that they would prefer to receive information through platforms such as Facebook and TikTok and are motivated by thematic events and promotions. In conclusion, it was determined that Blues Resto Bar has an attractive offer but needs to strengthen its digital presence, optimize its communication, and generate greater interaction with its audience. It is proposed to implement a structured digital marketing plan that includes dynamic visual content, weekly promotions, customer loyalty strategies, and strategic alliances with local actors. These actions will help consolidate the brand's positioning and increase the restaurant’s competitiveness in the Guaranda market.